Implementasi Program Kampung Keluarga Berencana (KB) di Desa Teluk Kelansam Kecamatan Sintang Kabupaten Sintang - Arpan, Arpan; Rochmawati, Ida; Madya, Faisal (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The Nawacita agenda, a priority agenda for President Joko.Widodo and his cabinet, consists of 9 flagship initiatives, and the power to implement them has been delegated to the National Family Planning Coordinating Board (BKKBN). According to the provisions of Law No. 23 of 2014 on Regional Government, specifically in the Division of Concurrent Government Affairs between the Central Government, Provincial Regions, and Regency/City Regions. in letter N (Division of Government Affairs in the Field of Population Control and Family Planning), a Family Planning Village Program (KB Village) policy was drafted in an effort to realize the development priority agenda. Decree of the Sintang Regent Number: 476/500/KEP-DKBP3A/2021 Concerning the Formation of a Regional Working Group (District Working Group) on Population, Family Planning, and Prosperous Family Development in Sintang District, particularly in Teluk Kelansam Village, Sintang District, mandated the establishment of the KKBPK in order to implement the KB Village Program at the district level. The goal of this research was to use the Charles O. Jones Theory to identify, describe, and evaluate the steps taken by the residents of Teluk Kelansam Village, Sintang District, Sintang Regency, as they implemented the KB Village Program policy. First, the findings indicate that the organization in question has the necessary institutional framework, personnel, financial resources, and physical facilities to function effectively. Second, application/application, which involves having a defined work program, work processes, and schedule of activities; third, interpretation, which includes compliance with rules, technical instructions, and implementation instructions.